Effects of Etiolated Slip Management on the Establishment, Fresh Tuber Yield and Yield-Related Attributes of White Guinea Yam, Dioscorea Rotundata Poir - Gyansa-Easmon, C.E. (Discovery and Innovation, 2000)
The "slip" of white guinea yam, Dioscorea rotundata Poir refer to the leafless sprout with the associated cormous structure that develops from the stored tuber when the dormancy period is over. Under dark storage conditions, these slips are etiolated, whitish or pale yellowish, being devoid of chlorophyll. At the end of 3 weeks of presprouting in topsoil, they attained a dry matter content of 58.9%, representing a net increase in "morphogenetic efficiency" (ME) of 340.3%, compared to the unpresprouted. A field experiment elicited no significant fresh tuber yield differences between the "directly planted" and "prerooted" slips at 5 months after transplanting or planting. The "presprouted" ones produced significantly higher fresh tuber yield of 19.3 t/ha. The directly-planted, produced significantly superior tuber size of 362.6g relative to the presprouted or prerooted, although its number of tubers per h. of 24,785 was significantly lower than the 103,910 of the presprouted. The directly-planted and presprouted produced tubers largely in the conventional seed yam range (200-1000g). This was an indication that the etiolated slips - the presprouted form, could be a new source of planting material for commercial seed yam production. The plants exhibited a "bushy" canopy architecture rather than viny and thus staking may not be necessary.
Keywords: Dioscorea rotundata; Etiolated slips; Fresh tuber yield; Morphogenetic efficiency; White guinea yam